The Influence of Using Instagram @Official USU Account on Image and Public Trust at Universitas Sumatera Utara Medan - Siti Rahma Br Ginting; Mazdalifah; Dewi Kurniasih (International Journal of Scientific Multidisciplinary Research, 2024)
This study aims to determine the effect of the use of the Instagram account @official.usu on the image and public trust at the University of North Sumatra in Medan City and to determine the level of influence between the use of the Instagram account @official.usu and the image and public trust at the University of North Sumatra in Medan City. This research method uses a quantitative approach and is carried out in Medan Baru District which consists of 6 Villages. The theories used are public relations theory, new media, image and trust. Indicators of Instagram use consist of Context, Communication, Collaboration, and Connection, indicators of image consist of Personality, Reputation, Value, and Corporate Identity, indicators of trust consist of Ability, Integrity, and Benevolence. Sampling was carried out using the Stratified Proportional Sampling and Cluster Random Sampling techniques with a sample size of 400 people. Data were collected through Google Forms which were distributed to respondents. The research data were analyzed using the single table method, cross table, Spearman Rank hypothesis test, and correlation coefficient analysis